IgG4-Related Hypophysitis: Case Report and Literature Review - Decker, Lauren (Cureus, 2016)
IgG4-related hypophysitis is a rare, inflammatory process of the pituitary that mimics more commonly seen pituitary tumors. We report a case of IgG4-related hypophysitis in a 16-year-old female with diabetes insipidus who was found to have IgG4-related hypophysitis based on tissue diagnosis. This entity has not been previously described in a pediatric patient. Recognition of certain inflammatory processes of the pituitary may lead to alternative means of diagnosis and medical management without a biopsy.